Three Novel Species with Peptidoglycan Cell Walls form the New Genus Lacunisphaera gen. nov. in the Family Opitutaceae of the Verrucomicrobial Subdivision 4 - Rast, Patrick; Glöckner, Ines; Boedeker, Christian; Jeske, Olga; Wiegand, Sandra; Reinhardt, Richard; Schumann, Peter; Rohde, Manfred; Spring, Stefan; Glöckner, Frank O.; Jogler, Christian; Jogler, Mareike (Frontiers in Microbiology, 2017)
The cell wall of free-living bacteria consists of peptidoglycan (PG) and is critical for maintenance of shape as dissolved solutes cause osmotic pressure and challenge cell integrity. Surprisingly, the subdivision 4 of the phylum Verrucomicrobia appears to be exceptional in this respect. Organisms of this subdivision are described to be devoid of muramic or diaminopimelic acid, usually found as components of PG in bacterial cell walls. Here we describe three novel bacterial strains from a freshwater lake, IG15T, IG16bT and IG31T, belonging to a new genus in the subdivision 4 of Verrucomicrobia which we found to possess PG as part of their cell walls. Biochemical analysis revealed the presence of diaminopimelic acid not only in these novel strains, but also in Opitutus terrae PB90-1T, the closest described relative of strains IG15T, IG16bT and IG31T. Furthermore, we found that nearly all genes necessary for peptidoglycan synthesis are present in genomes of subdivision 4 members, as well as in the complete genome sequence of strain IG16bT. In addition, we isolated and visualized PG-sacculi for strain IG16bT. Thus, our results challenge the concept of peptidoglycan-less free-living bacteria. Our polyphasic taxonomy approach places the novel strains in a new genus within the family Opitutaceae, for which the name Lacunisphaera gen. nov. is proposed. Strain designations for IG15T, IG16bT and IG31T are Lacunisphaera parvula sp. nov.(=DSM 26814 = LMG 29468), Lacunisphaera limnophila sp. nov. (=DSM 26815 = LMG 29469) and Lacunisphaera anatis sp. nov. (=DSM 103142 = LMG 29578) respectively, with Lacunisphaera limnophila IG16bT being the type species of the genus.